Infant feeding knowledge, attitudes and practices of HIV-positive breastfeeding mothers - Kgabo M. Mabotja; Annette van Onselen; Reno E. Gordon (AOSIS, 2024)
Background: Assessment of infant feeding knowledge, attitudes and practices of human immunodeficiency virus (HIV)-positive breastfeeding mothers may determine compliance with the chosen feeding method. Aim: The study assessed knowledge, attitudes and practices on infant feeding among HIV-positive breastfeeding mothers. Setting: The study was conducted at five clinics in the Chief Albert Luthuli sub-district of Mpumalanga, South Africa. Methods: A descriptive cross-sectional study with a convenient sample of 155 HIV-positive breastfeeding mothers. Results: More than half of the participants (54.8%) were knowledgeable of exclusive breastfeeding in general. However, less than half were knowledgeable of exclusive breastfeeding in the context of HIV (46.5%), mixed feeding (28.4%) and replacement feeding (49.0%). Most participants (85.8%) reported that they were advised to exclusively breastfeed for 6 months, 61.3% intended to exclusively breastfeed for 6 months, and 29% intended to stop breastfeeding at 6 months. Most participants (64.5%) intended to introduce solids at 6 months, and for participants who intended to introduce solids before 6 months, 37.7% did not believe that exclusive breastfeeding was sufficient for the baby. Conclusion: Although most participants were knowledgeable about exclusive breastfeeding, there were misconceptions that required attention such as the lack of knowledge on exclusive breastfeeding in the context of HIV, mixed feeding and replacement feeding. Exclusive breastfeeding for 6 months was the most emphasised infant feeding practice. Contribution: This study builds on existing literature on infant feeding knowledge, attitudes and practices and provides a basis for interventions for improved exclusive breastfeeding rates.